TWENTY FIVE YEARS WITH COCONUT RESEARCH AND DEVELOPMENT A PERSONAL VIEW OF SIGNIFICANT EVENTS FROM 1968 TO 1993 - Hugh C. Harries (International Coconut Community, 1994)
In January 1968, the author joined the research department of the Coconut Industry Board, Jamaica as plant breeder. Twenty‑five years later, in July 1993, he completed a contract as plant breeder at the National Coconut Development Project, Tanzania. In between, he undertook coconut research and development work in a variety of situations. The twenty‑five year span coincides closely to that of the Asian Pacific Coconut community's own jubilee from 1969 to 1994. A twenty‑five year jubilee is a good excuse to look back on what has passed and review what has been learned. What events seemed to be important at different times during this period? What other, seemingly important events, turned out to be non‑starters? Can any recent events be identified that will affect future research and development? What follows are personal views. other people will have different ideas of what is important and‑what is not. But a twentyfifth anniversary is also a time to plan for the future. That is what APCC will be doing. Like APCC, the author intends to continue to take an interest in this, the most worthwhile of all crops.